2020
DOI: 10.1136/bmjresp-2020-000601
|View full text |Cite
|
Sign up to set email alerts
|

What effective ways of motivation, support and technologies help people with cystic fibrosis improve and sustain adherence to treatment?

Abstract: Introduction“What effective ways of motivation, support and technologies help people with cystic fibrosis improve and sustain adherence to treatment?” was identified as one of the James Lind Alliance Priority Setting Partnership’s top 10 research questions in cystic fibrosis (CF). Using electronic questionnaires, we aimed to gain a deeper understanding of this research priority.MethodThe work was led by the steering group representative of the UK CF community consisting of patients, carers and healthcare profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Nonetheless, they underlined that relationships with and support from HCPs remained important and the PRO solution could not entirely replace in-person meetings. This was also the finding of the other study [16] , which identified patients’ families and CF teams as key support networks.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Nonetheless, they underlined that relationships with and support from HCPs remained important and the PRO solution could not entirely replace in-person meetings. This was also the finding of the other study [16] , which identified patients’ families and CF teams as key support networks.…”
Section: Discussionsupporting
confidence: 83%
“…Another study by Calthorpe et al. [16] highlighted the need to focus on developing interventions that simplify care and reduce treatment burden. Overall, the participants agreed that the PRO solution supported individualized outpatient care as they experience CF as a dynamic disease that requires a flexible approach to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A previous survey, completed prior to the pandemic, demonstrated that technology is being used by a subset of the CF community to aid treatment management. Health professionals tended to be more enthusiastic about the technology than pwCF [11] . Indeed, Solomon et al.…”
Section: Telehealth After the Pandemic: Will The Inverse Care Law Apply?mentioning
confidence: 99%
“…A previous survey, completed prior to the pandemic, demonstrated that technology is being used by a subset of the CF community to aid treatment management. Health professionals tended to be more enthusiastic about the technology than pwCF [11] . Indeed, Solomon et al also describe a level of uncertainty in the CF community as to whether mainly in person, online or a combination of the two modalities was most appropriate.…”
mentioning
confidence: 99%
See 1 more Smart Citation